The Taxonomic Measure of Sustainable Development of Metropolitan Areas in Poland - Koszel, Maciej; Bartkowiak, Piotr (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The article examines the problem of measuring the sustainable development of local self-government units that constitute metropolitan areas (MA) in Poland. In order to evaluate and compile sustainable development rankings, a taxonomic method, Hellwig̛s standard method, was chosen. Drawing on Central Statistical Office (GUS) data from 2015, an assessment was made of 345 municipalities and cities forming eight Polish metropolitan areas in five dimensions: economic, social, ecological, spatial and overall (mega aggregate). The level of sustainability of local government units shows a clear dependence on their location, population, type and area. A higher level of sustainable development in the economic, social and spatial aspects is demonstrated by urban units located in the central zone and with a population of over 50,000 inhabitants (Warsaw MA). With respect to environmental sustainability rural, peripheral and smaller populations (Szczecin MA and Lodz MA) show better assessment scores.